In Vitro Mesenchymal Progenitor Cell Expansion is a Predictor of Transplant-related Mortality and acute GvHD III-IV After Bone Marrow Transplantation in Univariate Analysis: A Large Single-Center Experience. Issue 1 (January 2019) - Berger, Massimo; Mareschi, Katia; Castiglia, Sara; Rustichelli, Deborah; Mandese, Alessandra; Migliore, Enrica; Fagioli, Franca
Abstract : Mesenchymal stromal cells (MSCs) are multipotent stem cells able to differentiate into mesenchymal origin tissue and support the growth of hematopoietic stem cells. In order to understand the role of MSCs infused in bone marrow grafts, 53 consecutive patients were analyzed for engraftment, acute and chronic graft-versus-host disease (GvHD), transplant-related mortality (TRM), relapse incidence, and overall survival. The MSC content was measured as MSC expansion at the second passage. When in vitro–expanded MSC (cumulative population doubling at second passage, cPDp2) values were stratified according to the median value (2.2-fold increase), the univariate analysis showed a significant difference in TRM (23% vs. 3.8%, P =0.05.) and in acute GvHD III-IV incidence (12% vs. 4%, P =0.04), while the multivariate analysis did not confirm its independent role. No clinical parameters in donors and recipients were identified as predictors of cPDp2 expansion. Our study suggests a role for short-term ex vivo–expanded MSCs in reduced aGVHD III-IV incidence and TRM in univariate analysis. A multicenter, larger study is warranted to confirm these data.